Power & posterity : American art at Philadelphia's 1876 Centennial Exhibition - Orcutt, Kimberly (The Pennsylvania State University Press, 2017)
"Explores the art exhibits at the 1876 Centennial Exhibition in Philadelphia, along with the circumstances of their creation, the ideological positions expressed through their installation, and the responses of viewers, including critics, collectors, and the general public"--Provided by publisher